How does financial communication affect millennials’ online shares purchase intention? - De Costa, Feroz; Aziz, Norzalita; Wan Hussain, Wan Mohd Hirwani; Mohd Hasan, Nurul Ain (Human Resource Management Academic Research Society, 2020)
The main aim of this article is to identify the influence of online financial communication disseminated through social media on brand attitude and the intention of millennials to purchase Shariah-compliant shares in Malaysia. A convenience sampling procedure using online questionnaires was used to test seven hypotheses based on prior literature. The partial least squares structural equation modelling (PLS-SEM) technique and the SmartPLS 3 tool was used to analyse this study. The findings of this study highlighted that user generated content (UGC) and firm generated content (FGC) positively influence brand attitude. By incorporating the theory of reasoned action and the signalling theory, the result showed a contradictive outcome to previous literature. UGC has no direct effect on the purchase intention of Shariah-compliant online stocks. This study suggests that companies should further comprehend the branding of their companies with the use of their official social media pages by increasing a positive attitude towards their brand.